Loss Quantization of Reflectarray Antenna Based on Organic Substrate Materials - H. I Malik; M. Y Ismail; Sharmiza Adnan; S. R Masrol (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper presents novel loss quantization of reflectarray elements based on organic substrate materials. Three differently composed substrate materials derived from recycled materials have been characterized for their dielectric properties using a broadband analysis technique. The materials show low dielectric permittivity values of 1.81, 1.62 and 1.84 for X-band frequency range. In order to estimate the reflection loss of for the three substrates a mathematical relation has been established using empirical data generated by computer simulated models. The reliability of the proposed model has been established by simulation and fabrication of unit reflectarray rectangular patch elements on three proposed substrate substrates. A broadband frequency response has been depicted by scattering parameter analysis of unit elements with 10% fractional bandwidth of 312, 340 and 207 MHz for RCP50, RCR75 and RNP50 substrate respectively.